ANALISIS KINERJA KEUANGAN DAN POTENSI KEBANGKRUTAN SERTA PENGARUHNYA TERHADAP HARGA SAHAM PADA PERUSAHAAN TERBUKA SEKTOR TELEKOMUNIKASI DI BEI - Benny Dwi Kifana; Kamaliah ' '; Ediyanus Herman Halim (Program Studi Pendidikan Ekonomi Universitas Riau, 2015)
This research was conducted at the Telecommunications sector companies listed inIndonesia Stock Exchange, with secondary data . This study aims to determine theeffect of the financial performance and the potential bankruptcy of either partially orsimultaneously on stock prices. Data analysis techniques in this study using adescriptive method and multiple regression analysis to determine the effect of twoindependent variables on the dependent variable. This study also using factoranalysis to determine the most contributed indicator for each independent variables.Financial performance is measured based on the Ministry of Finance of the Republicof Indonesia No. 826/KMK 013 / 1992. It involves the calculation of liquidity ratios,profitability ratios , solvency ratios, profit margin ratio and operating ratio. While thepotential bankruptcy was measured with Fulmer’s bankruptcy model. This studyusing financial statement data for 5 consecutive years from 2008 to 2012 onTelecommunications company listed in Indonesia Stock Exchange.Based on the results of this study, we can concluded that the financial performanceand the potential bankruptcy by partially and simultaneously have a significant effecton the stock price at the telecommunications company listed on the Indonesia StockExchange during the study period of 2008-2012. During this period, thetelecommunications companies on average have an unhealthy financialperformance. This shows that the telecommunications industry in Indonesia has aclimate of intense competition. On the other hand, the potential bankruptcy of thecompany tend to be quite good and it implies that the company can still survive amidthe intense competition . This certainly indicates that the telecommunicationsindustry can still thrive because it is driven by technological developments and thegrowing number of users of telecommunications.Keywords : Potential bankruptcy fulmer models and financial performance